Kemampuan Auditor Mendeteksi Kecurangan: Sebuah Analisa Faktor: Studi Kasus Pada KAP Tanzil di Surabaya - Bunga Yulia, Monica; Setiono, Hari; Isnaini, Nurdiana Fitri (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2025)
The purpose of this study was to determine the partial significant effect of auditor experience, professional skepticism and auditor competence on the auditor's ability to detect fraud at the KAP Tanzil in Surabaya. This study includes quantitative research with primary data sources. The population of this research is 20 auditors who work at KAP Tanzil in the city of Surabaya, with the saturated sample method. The independent variable of this study is the auditor's experience (X1), professional skepticism (X2), competence (X3) and the dependent variable is the auditor's ability to detect fraud (Y). The research instrument is a questionnaire with Likert scale measurements which are processed using SmartPLS ver3. The results of this study are the auditor's experience variable resulting in a p-value of 0.012 and a t-statistic of 2.534. Then, professional skepticism resulted in a p-value of 0.028 and a t-statistic of 2.205. While the competence variable produces a p-value of 0.006 and a t-statistic of 2.744. Each dependent variable has a p-value (p < 0.05) and a t-statistic (t > 1.96) which means a significant alpha of 5% resulting in a positive effect on the independent variable. The conclusion is that the variables of auditor experience, professional skepticism and competence have a partial significant effect on the auditor's ability to detect fraud at the KAP Tanzil in Surabaya.